Transient transfection and expression of eukaryotic membrane proteins in Expi293F cells and their screening on a small scale: application for structural studies - Krasnoselska, GO; Dumoux, M; Gamage, N; Cheruvara, H; Birch, J; Quigley, A; Owens, RJ (Springer Nature, 2021)
Cancers, neurodegenerative and infectious diseases remain some of the leading causes of deaths worldwide. The structure-guided drug design is essential to advance drug development for these important diseases. One of the key challenges in the structure determination workflow is the production of eukaryotic membrane proteins (drug targets) of high quality. A number of expression systems have been developed for the production of eukaryotic membrane proteins. In this chapter, an optimized detailed protocol for transient transfection and expression of eukaryotic membrane proteins in Expi293F cells is presented. Testing expression and purification on a small scale allow optimizing conditions for sample preparation for downstream structural (cryo-EM) elucidation.